Moje życie, moja walka Jarosława Mogutina - spowiedź pochopna czy przedwczesna? - Ojcewicz, Grzegorz (Acta Polono-Ruthenica, 2004)
The subject of this article is an analysis of the text My life, my fight (1974) by Jaroslav Mogutin considering its autobiographical value. The present work appears to be a specific catalo gue of the most important events from Mogutin’s point of view, from his difficult childhood in Russia to his forced New-York emigration. Among the files of Mogutin’s catalogue the confession connected with making real his homosexual likes takes a particular place. Family rows and breaking the law form a peculiar background to it. Mogutin is painfully sincere in describing his perverted erotic desires and persistent thoughts overfilling his head. He hopes to succeed in expressing the very essence of his individualism in that life-time epitaph.